A study on the perceptions of the Institute of Library and Information Science students on library and information science electives - Wong, Jose Raphael M; Carcellar, Marie Desiree R. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
The field of Library and Information Science is often subjected to developments. In order to adapt to these changes, the UP Institute of Library and Information Science (ILIS) offers electives in information systems, health/medical librarianship, law librarianship, archives and records management and general librarianship for the Bachelor of Library and Information Science (BLIS) program.
This study aimed to determine : (1) How BLIS student perceived the effects of LIS electives on the BLIS curriculum; (2) The factors that contributed to the choice of LIS track of BLIS students; (3) The factors that contributed to the choice of LIS electives of BLIS students; (4) The strengths of LIS electives, as perceived by BLIS students; and (5) The weaknesses of LIS electives, or the problems encountered concerning them, as perceived by BLIS students.
This study found out that: (1) BLIS students believed that LIS electives in different LIS tracks strengthened the BLIS curriculum and they considered LIS electives to be important for the BLIS curriculum. They believed that the other LIS subjects will not be enough for the program if LIS electives are not offered. (2) Among the factors that affected the choice of tracks of BLIS students, "Interest in the field or track" was the top choice followed by "Job opportunities related to the track". (3) In choosing LIS electives, most BLIS students considered their "interest in the LIS tracks" more than the "availability of electives or convenience in schedule". (4) Most BLIS students believed that LIS tracks were well-represented by the LIS electives offered under them; they gained enough knowledge regarding their tracks through the LIS electives; LIS electives helped them in preparing for their chosen tracks; and LIS electives provided the present academic needs of BLIS students. (5) Most BLIS students believed that LIS electives only provide general information of LIS tracks. The respondents suggested that: (a) More electives should be offered on each track, (b) More electives should be offered every semester, (c) Information regarding the different LIS tracks should be discussed with new BLIS students, (d) LIS electives should allow for more specialization, (e) For the Information Systems track, more programming languages should be taught, (f) For Archives and Records Management, laboratory subjects should be offered, especially for subjects on conservation, and more practical exercises should be given to students, (g) For Law librarianship, legal bibliography should be a prerequisite to legal research.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Institute of Library and Information Science -- Students; Library science; Information science